GROWTH OF MULTIDISCIPLINARY SCIENCE IN THE PERIPHERY - O’Connor, Kevin; Sharp, Robert (European Scientific Journal, ESJ, 2014)
This paper examines practice, growth and research associated with numerous experiential science, field studies and related place-based activities incorporated in a number Indigenous and rural communities in northern Canada. These approaches to science are presently being applied in the public school systems of the northern Canadian Territories (Yukon and Nunavut), and in numerous Cree and Dene Nation reserve schools in the northern Provinces of Alberta, Saskatchewan and Quebec. The research has followed students over a range of years following their engagement in these programs exploring their ongoing participation in the field of science and in community affairs. The capacity for communities to direct and manage their own educational programs has been a central concern particularly in rural, remote and Indigenous communities. Characteristics of peripheral communities provide opportunities to initiate and manage various conditions of social change. This paper identifies those characteristics that favor educational approaches that require changes in how schools organize time, teaching staff, and curriculum offerings. These include experiential and place-based science approaches. These approaches have shown a greater engagement and improved outcomes of Indigenous and rural students.